2004
DOI: 10.1016/j.cardiores.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits ox-LDL-mediated LOX-1 expression and metalloproteinase-1 in human coronary endothelial cells

Abstract: These observations suggest that aspirin inhibits ox-LDL-mediated LOX-1 expression and interferes with the effects of ox-LDL in intracellular signaling (p38MAPK activation) and subsequent MMP-1 activity. These novel effects of aspirin may complement its platelet inhibitory effect in acute myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 41 publications
1
66
2
1
Order By: Relevance
“…LOX-1 activation has also been shown to activate NADPH oxidase and subsequent redox signals involving MAPKs and NF-B in human endothelial cells. 14,38 We found that the small proangiogenic concentrations of oxLDL that led to LOX-1 expression also induced NADPH oxidase (both gp91 phox and p47 phox subunits), activated MAPK (both p38 and p44/42 components) and NF-B p65, and resulted in VEGF expression. Our experiments show that VEGF expression induced by oxLDL is a major mechanism of capillary tube formation from HCAECs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…LOX-1 activation has also been shown to activate NADPH oxidase and subsequent redox signals involving MAPKs and NF-B in human endothelial cells. 14,38 We found that the small proangiogenic concentrations of oxLDL that led to LOX-1 expression also induced NADPH oxidase (both gp91 phox and p47 phox subunits), activated MAPK (both p38 and p44/42 components) and NF-B p65, and resulted in VEGF expression. Our experiments show that VEGF expression induced by oxLDL is a major mechanism of capillary tube formation from HCAECs.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have demonstrated that LOX-1 activation induces oxidative stress 10 and oxidative stress in turn stimulates LOX-1 expression, 14 suggesting a positive feedback loop between oxidative stress and LOX-1 expression. LOX-1 activation has also been shown to activate NADPH oxidase and subsequent redox signals involving MAPKs and NF-B in human endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimentally, however, no studies have been performed to investigate the potential use of NSAIDs as MMPs inhibitors in the MI setting. Aspirin, the most commonly used NSAID among patients with myocardial infarction and heart failure, suppresses MMP-1 in isolated human coronary endothelial cells but did not affect MMP-2 or -9 levels [140,141].…”
Section: 25mentioning
confidence: 93%
“…We have observed that aspirin, in a dose-and timedependent fashion, reduced ox-LDL-mediated LOX-1 expression, MMP-1 expression and activity, p38MAPK activation and superoxide anion generation in human coronary artery endothelial cells (15). Interestingly, we have observed that the treatment of human coronary artery endothelial cells with salicylate, but not indomethacin, resulted in effects similar to those of aspirin (15).…”
Section: Effect On Oxidative Stressmentioning
confidence: 72%